Upaya Peningkatan Pemahaman Konsep Pecahan Melalui Program Bimbingan Belajar Matematika Bagi Siswa Kelas VI SDN 1 Semaya - Khumaeroq Alya Yunisa; Sri Supiyati (Universitas Mataram, 2026)
Understanding fraction concepts is one of the fundamental competencies in mathematics that remains challenging for elementary school students, particularly sixth-grade students. The purpose of this activity was to provide mathematics tutoring for sixth-grade students at SDN 1 Semaya to help them overcome difficulties in learning mathematics. The implementation method of this community service activity consisted of five main stages: (1) planning and preparation, which included obtaining permission to conduct the community service activity, carrying out an initial observation to identify mathematics topics that required tutoring, preparing the instructional materials needed for the tutoring activities, and determining the schedule for the tutoring program; (2) administering a pretest to identify students’ initial mathematical abilities before the tutoring activities were conducted; (3) implementing the mathematics tutoring activities; (4) administering a posttest to assess students’ mathematical abilities after the tutoring activities; and (5) evaluation. The results of this activity indicate that the mathematics tutoring program for sixth-grade students at SDN 1 Semaya was effective in helping students overcome difficulties in learning mathematics.